Untying Moral Efficacy and Meaningfulness in Promoting Students’ Social Entrepreneurial Intentions: The Mediating Role of Positive Reciprocity - Xiang, Jian; Zhang, Yanjun (Frontiers in Psychology, 2022)
This study chooses to describe social entrepreneurship as a social mission that enables business students to identify opportunities to launch start-ups and social enterprises by understanding the nature of social responsibility and fostering a reciprocal attitude to solve social issues. We collected data on students from different business schools in mainland China through a structured questionnaire (n=326) and analyzed them through structural equation modeling. The results show that moral efficacy and meaningfulness are positively related to positive reciprocity, which leads to students’ social entrepreneurial intentions. The study concluded that potential social entrepreneurs should take ethical courses as part of their training to help them develop a responsible mentality and social entrepreneurial aspirations. On this basis, the practical and theoretical significance of this study is proposed, and its limitations and future development directions are pointed out.